Analysis of Differences in Student Learning Satisfaction Levels Against ONLINE and OFFLINE Learning Faculty of Psychology UIN MALIKI Malang - Candra Ayu, Selly; Arif Furqon, Muhammad (Jurnal KESANS : Kesehatan dan Sains, 2021)
This research aims to find out how much the level of difference in learning satisfaction to the online and offline learning process of the Faculty of Psychology UIN MALIKI Malang. Factors that affect learning satisfaction, namely: Tangible  Aspects (Physical Evidence): Infrastructure Facilities, Teaching Media, Reliability Aspects (Reliability): Lecturer Reliability in teaching, Responsiveness Aspects: Lecturer Responsiveness, Assurance Aspects (Assurance): Lecturer's treatment of students and Empathy Aspect (Empathy): Understanding of student interests. This research was conducted on students of the Faculty of Psychology with a total of 134 subjects. Data collection tool in the form of a learning satisfaction questionnaire consisting of 40 items. Data analysis is carried out with the T-Test sample paired statistics technique, with the help of the SPSS statistics program version 28. From the results of the analysis of research data obtained correlation value 0.316. Based on the results of the analysis on this study, it can be concluded that there is a difference in student satisfaction of the Faculty of Psychology UIN Maulana Malik Ibrahim Malang between before the pandemic and at the time of the pandemic, both in the aspects of tangible, Reliability, Responsiveness, Assurance and empathy. Nevertheless, differences in satisfaction in Tangible  aspects were not felt significantly between before and during the pandemic. This shows that students feel more satisfied studying online than offline.